A Multi-Angle Method for Simultaneous Retrieval of Aerosol Optical Depth and Bidirectional Reflectance Over Case II Waters - Han, Zeying; Cheng, Tianhai; Gu, Xingfa; Shi, Shuaiyi; Li, Xiaoyang; Bi, Kaiyi (Frontiers in Environmental Science, 2022)
Retrieval of aerosol optical depth (AOD) and bidirectional reflectance over Case II waters is a challenging task because of the optical complexity of water and the significant influence of atmospheric scattering. We present a simultaneous retrieval algorithm, coupled with a bidirectional reflectance distribution function (BRDF) model centered on the water’s Inherent Optical Property (IOP), to retrieve AOD and bidirectional reflectance based on multi-angle measurements from the Multi-angle Imaging SpectroRadiometer (MISR) sensor. The algorithm was evaluated through retrievals performed in the proximity of four AERONET sites characterized by various water types. Consistency was observed between the results and in situ measurements. Accurate AODs can be retrieved, and atmospheric overcorrection can be avoided when obtaining remote sensing reflectance. Furthermore, the normalized remote sensing reflectance derived from our results showed a good correlation with the AERONET-OC products derived using the IOP-based correction approach. Our study provides theoretical support for future quantitative remote-sensing studies.